Reversible Inferolateral ST-Segment Elevation Associated with Small Bowel Obstruction - Ankit Upadhyay; Sudheer Chauhan; Umair Jangda; Vipul Bodar; Ahmed Al-Chalabi (Case Reports in Medicine)
ST-segment elevation is an important and alarming electrocardiographic sign that necessitates immediate attention but does not always indicate that the primary pathology is cardiac in origin. It needs to be interpreted in the clinical context as several pathological conditions involving especially gastrointestinal tract may lead to delayed diagnosis and treatment as well as complications from invasive unnecessary interventions. We present two patients, a 64-year-old male and a 71-year-old female, who were admitted to the emergency room of a community-based hospital with similar complaints of worsening epigastric abdominal pain and were diagnosed later with small bowel obstruction. Both patients reported a history of abdominal surgeries in the past. Also in both patients the ECG showed signs of ST-segment elevation in inferior and lateral leads. These ECG changes were related to the intra-abdominal pathology as no evidence of contributing coronary artery disease could be found. In addition, prompt resolution of ST-segment elevation was seen after surgical treatment. The pathophysiological etiology of electrocardiographic changes accompanying small bowel obstruction is yet to be explored.